Menelusuri Urgensi dan Beragam Lagu Dolanan untuk Anak Usia Dini - Mahfudiyah, Umi; Priambada, Muhammad; Shofwan, arif muzayin; Farantika, Dessy (Journal of Childhood Education, Development and Parenting, 2023)
Javanese dolanan songs are songs that can be sung for early childhood while playing and learning. This is significant with the principles of early childhood education, namely learning while playing and playing while learning. This qualitative descriptive research with literature study examines the urgency and variety of play songs for early childhood. The data analysis technique uses content analysis by sorting out data according to the research problem. This study resulted in the following conclusions. First, the urgency of Javanese dolanan songs for early childhood, among others: can shape the character of early childhood as a whole; contribute practically for children and the community to develop policies related to national defense, development of creative industries, as well as local wisdom; can develop the values ​​of honesty, openness, and wisdom; and can be used for the development of national character. Second, a variety of Javanese dolanan songs that can be implemented in early childhood, including: Gundul Pacul, Padhang Bulan, Cublak Suweng, Menthog-Menthog, Jago-Jago, Kidang Talun, Tikus Pithi, Tikus Buntung, Gotri, Gajah Belang, Taman Sari, Gajah, Pitik Tukung, Bulan Gedhe, Kupu Kuwi, Lumbung Desa, Kodhok Ngorek, Jaranan, Te Kate Dipanah, Sluku-Sluku Bathok, Dhondhong Apa Salak, Endhog-Endhogan, Ana Tamu, Duwe Tangan Loro, Kuwi Apa Kuwi, Siji Loro Telu, and Sak Iki Aku Wis Gedhe